Selection the stabilization/solidification process and selection the binders and reagents depending on the type of waste material in the function of environmental protection - Marjanović Vesna M.; Ivanović Aleksandra T. (Mining and Metallurgy Engineering Bor, 2015)
This paper presents the overview and method of selection the stabilization/solidification process, considering that a very long time suitable for treatment the hazardous waste in order to protect the environment. Selection the method for stabilization/solidification (S/S) the hazardous waste depends on the type of waste, content of hazardous and harmful components and it is applied as the method of pretreatment the hazardous waste before disposal into landfill. Also, in this paper, the data are systemized that related to the process of stabilization and solidification, the basic concepts relating to these processes, as well as the phase of collecting the information on processing and verification the process S/S. This paper provides the possibilities of selection the additives depending on the type of waste material. Using the technological process of stabilization/solidification (S/S) and corresponding additives, the waste material is transformed into inert material independently of the individual values of metal solubility or components in waste. Also the fact of great importance is that some physical or chemical parameters of solidified waste material (permeability, resistance to compression) can be easily controlled by selection of chemical additive and its share in the mixture (waste/additives). The process of S/S has a reasonable use in liquid waste or waste with a high content of liquid phase with impossible disposal on the landfills without prior treatment. These processes can be performed in-situ - on the location of hazardous waste and ex-situ - in the facilities that are designed for that purpose.